Review on Buddhism for Peace and Conflict Resolution (Research Nepal Journal of Development Studies, 2023)
Buddhism is a symbol of peace, harmony, and well-being. It focuses on the development of the inner mind’s enlightened qualities by cessation of suffering and conflict. Buddha taught the four noble truths for understanding these human sufferings. If we don’t understand our suffering it is very difficult to empathize with others. Nowadays, Buddhism is becoming socially engaged, and its ideals have helped to inform a variety of approaches to conflict resolution. The paper is prepared for the dissemination of the essence of Buddhism for social and practical life. This workout has been done to enrich academic standards by presenting general issues, problems, findings, and recommendations written under the research methodologies. How Buddhism defines the cause of conflict, which suttas are found for conflict resolution, and what are the Buddhist concept of peacebuilding and the way to conflict resolution are the major problems of the study and its attribution is applied to social harmony.